Vibration Attenuation by a Combination of a Piezoelectric Stack and a Permanent Magnet - A. Nandi; S. Neogy; S. Bhaduri; H. Irretier (Shock and Vibration)
The present work proposes a non-contact vibration attenuator made up of a permanent magnet mounted on a piezoelectric stack. Two such actuators are made to work simultaneously in a 'twin-actuator' configuration. It is conceived that a controlled change in the gap between the actuator and the structure is capable of attenuation of vibration of the structure. This appropriate change in gap is achieved by controlled motion of the piezoelectric stacks. It is shown that the actuator works as an active damper when the extension and contraction of the actuators are made proportional to the velocity of the beam. The resolution of extension of a piezoelectric stack is in the order of nanometers. Thus in the proposed actuator the force of actuation can be applied with great precision. This actuator is also attractive for its simple constructional feature.